Conversion of fibrinogen to fibrin induced by preferential release of fibrinopeptide B - Dyr, J E; Blombäck, B; Hessel, B; Kornalík, F (Biochimica et biophysica acta, 1989)
Fibrin clot-promoting enzyme preferentially releasing fibrinopeptide B from fibrinogen was isolated from the crude venom of Agkistrodon contortrix and its mode of action was studied in detail. A purification procedure involving affinity chromatographies on immobilized lectin and arginine removed plasmin-like and kallikrein-like activities towards low-molecular-weight chromogenic substrates. Fibrin-promoting enzyme cleaved off only fibrinopeptides A and B from fibrinogen. The initial relative rate of release of fibrinopeptide B/fibrinopeptide A depended strongly on the presence of Ca2+. In the absence of Ca2+ the amount of fibrinopeptides released by fibrin-promoting enzyme at the gel point was greater. Fibrinopeptide B was no longer released before fibrinopeptide A from the non-polymerizing N-terminal disulphide knot of fibrinogen. Catalyzed by activated factor XIII, complete gamma-dimer and alpha-polymer formation was observed in fibrin from which only 23% of fibrinopeptide A, but 100% of fibrinopeptide B was released by fibrin-promoting enzyme. gamma-dimer formation markedly preceded alpha-polymer formation. These results strongly imply a similar overall arrangement of monomer molecules in this fibrin when compared with a thrombin-induced fibrin in which fibrinopeptide A is released before fibrinopeptide B. These observations support the concept that on fibrinopeptide B release from fibrinogen polymerization sites are exposed which reinforce the sites exposed on the release of fibrinopeptide A.
Keywords: fibrinogen; Electrophoresis, Polyacrylamide Gel; Fibrinopeptide A; serinové endopeptidasy; jedy chřestýšů; Kinetics; Serine Endopeptidases; Fibrinopeptide B; vysokoúčinná kapalinová chromatografie; Fibrin; lidé; Factor XIII; Crotalid Venoms; vápník; Macromolecular Substances; Chromatography, High Pressure Liquid; molekulová hmotnost; Calcium; faktor XIII; fibrin; Chromatography, Affinity; fibrinopeptid A; makromolekulární látky; fibrinopeptid B; Fibrinogen; Molecular Weight; elektroforéza v polyakrylamidovém gelu; kinetika; chromatografie afinitní; Humans